Removal of Highly Concentrated Methylene Blue Dye by Cellulose Nanofiber Biocomposites - Sanchez-Poblete, J; Santander-Meyer, R; Roa-Ruiz, K; Oyarce-Riveros, E; Boulett-Neira, A; Boulett-Neira, A (Elsevier B.V., 2023)
The contamination of water by dyes in high concentrations is a worldwide concern, and it has prompted the development of efficient, economical, and environmentally friendly materials and technologies for water purification. The hydration and adsorption capacity for methylene blue (MB) in biocomposites (BCs) based on cellulose nanofiber (CNF) (0 to 2 wt%) were studied. BCs were synthesized through a simple and straightforward route and characterized by spectroscopy, microscopic techniques and thermogravimetric analysis, among others. Hydration studies showed that BCs prepared with 2 wt% of CNF can absorb large volumes of water, approximately 2274 % in the case of poly 2-acrylamide-2-methyl-1-propanesulfonic acid (PAMPS)-CNF and 2408 % in poly sodium 4-styrene sulfonate (PSSNa)-CNF. These BCs showed outstanding adsorption capacity for highly concentrated MB solutions (4536 mg g−1 PAMPS-CNF and 11,930 mg g−1 PSSNa-CNF). It was confirmed that the adsorption mechanism is through electrostatic interactions. Finally, BCs showed high MB adsorption efficiency after several sorption-desorption cycles and on a simulated textile effluent. Furthermore, the theoretical results showed a preferential interaction between MB and the semiflexible polymer chains at the lowest energy setting. The development and study of a new adsorbent material with high MB removal performance that is easy to prepare, economical and reusable for potential use in water purification treatments was successfully achieved. © 2023 Elsevier B.V.